The Reality of Upper Primary School Students’ Use Of "Distance Learning" Tools During Crises from the Teachers’ Perspective in Al-Batuf Area – Palestine 1948 - Shehadeh, Haifa Mahmood (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate the differences in teachers’ perceptions of distance learning during crises across various domains (technical, human, pedagogical, administrative, cognitive, behavioral, and psychological), as well as to examine these perceptions according to demographic variables such as gender, age, academic qualification, and years of experience. This study adopted a descriptive-analytical approach. The study sample consisted of 120 teachers from the upper primary stage in the Batuf region of Palestine (1948), all of whom had experience with distance learning during crisis periods. A questionnaire, developed based on the study objectives and previous literature, was used as the research instrument, and its validity and reliability were confirmed prior to administration. The results indicated that teachers rated the reality of upper primary students’ utilization of distance learning tools during crises at a moderate level (M = 3.39), with the cognitive domain achieving the highest rating (M = 4.26). Moreover, no statistically significant differences were found in teachers’ evaluations according to demographic variables such as age, gender, experience, and academic qualification, indicating a minimal overall impact of these factors on teachers’ perceptions. Based on the findings, the study recommends intensifying practical training programs to enhance teachers’ technical and pedagogical competencies, as well as developing innovative teaching strategies to increase student engagement and participation in distance learning.